Gender training manual for development workers in crop-animal system - Vargas, D.S.; Porciuncula, L. Fe; Kollin, E.W. (Central Luzon State University, 2004)
This gender training manual is developed to help Development workers in crop-animal system apply gender concepts, tools and techniques to practical work. The ultimate hope is to harness the full potentials of women and men in the Development process. In Southeast Asia and China where the Crop-Animal Systems Research Network (CASREN) project is being implemented, men and women do play active roles in crop-animal systems integration. However, the pursuit of ensuring that Development interventions better meet the needs of women remains a big concern. Women still need to get empowered so that they can fully participate in the Development process on equal terms with men, both as beneficiaries and agents of change. Mainstreaming gender related concerns and issues in the Development process is very apparent and there is a need to sensitize Development workers and other practitioners who can influence planning and implementation of Development programs and projects toward a strong gender orientation. This manual is divided into six modules; viz; concepts on gender and Development; situation of women in CASREN country program areas; gender in agriculture; national policies and programs for the advancement of rural women; gender framework for Development planning; and monitoring and evaluation of gender Development programs.